Infrared spectra reveal box-like structures for a pentamer and hexamer of mixed carbon dioxide–acetylene clusters. Issue 3 (28th August 2015) - Rezaei, Mojtaba; Norooz Oliaee, J.; Moazzen-Ahmadi, N.; McKellar, A. R. W.
Abstract : The hexamer (CO2 )4 –(C2 H2 )2 is characterized by its high-resolution infrared spectrum. Abstract : Except for a few cases like water and carbon dioxide, identification and structural characterization of clusters with more than four monomers is rare. Here, we provide experimental and theoretical evidence for existence of box-like structures for a pentamer and a hexamer of mixed carbon dioxide–acetylene clusters. Two mid-infrared cluster absorption bands are observed in the CO2 ν 3 band region using a tunable diode laser to probe a pulsed supersonic jet. Each requires the presence of both carbon dioxide and acetylene in the jet, and (from observed rotational spacings) involves clusters containing about 4 to 7 molecules. Structures are predicted for mixed CO2 + C2 H2 clusters using a distributed multipole model, and the bands are assigned to a specific pentamer, (CO2 )3 –(C2 H2 )2, and hexamer, (CO2 )4 –(C2 H2 )2 . The hexamer has a box-like structure whose D 2d symmetry is supported by observed intensity alternation in the spectrum. The pentamer has a closely related structure which is obtained by removing one CO2 molecule from the hexamer. These are among the largest mixed molecular clusters to be assigned by high-resolution spectroscopy.